Applied Microsoft business intelligence - Leblanc, Patrick (John Wiley & Sons, Inc., 2015)
This book shows you how to use the Microsoft business intelligence building blocks to construct synergetic and complete solutions to suit any organization. Organized chronologically by implementation order, it guides you through the data layer, data transformation and quality, the semantic layer, and the presentation layer, and ties it all together with comprehensive case studies. Focusing on best practices rather than specific tools keeps your skills relevant beyond the 2014 SQL release. Comprehensive explanations including architecture, strengths and weaknesses, and practical applications bring you fully up to speed quickly